Legal Protection for Agents as Business Partners in Insurance Product Marketing Cooperation Agreements Carried Out with Life Insurance Companies (Study of District Court Decision No. 939/Pdt.G/2023/PN-Mdn) - Novica Anggrayani Pangaribuan; Joiverdia Arifiyanto; Mulhadi (CERED Indonesia Institute, 2025)
This study discusses the regulation of the position of insurance agents as business partners in cooperation agreements with life insurance companies, especially regarding the aspect of legal protection in the event of unilateral termination of the relationship. Although agents are often referred to as